Bartholomeides’s Portrayal of the Enlightenment Ruler - Brtáňová, Erika (Poznańskie Studia Slawistyczne, 2018)
The intensity of the literary movement that took place in the Slovak territory integrated within the Kingdom of Hungary due to the Enlightenment policy of the ruler Joseph II can be properly illustrated by the genre-varied works of Ladislav Bartholomeides, an Evangelical priest and teacher. His first literary work Rozmlouvání Jozefa Druhého s Matějem Prvním Korvínus řečeným v království zemřelých, 1790 (The Conversation of Joseph II with Matthias I, Called Corvinus in the Kingdom of the Dead, 1790) is, in the first place, a significant evidence of the impact of the antique dialogue on the Slovak literary works. Bartholomeides updates the conversation of the dead, a popular genre form of the Enlightenment literature. Based on his predecessors’ assertions, he shapes the image of Joseph II as a clever and kind-hearted ruler. The Hungarian monarchs that Joseph II meets after his death defend his Enlightenment reforms. A critical reflection can be heard from Joseph’s lips. In terms of the contemporary Enlightenment writing, Bartholomeides put emphasis on the aesthetic category of “ingenuity”. In his attempt at an objectified interpretation of Joseph II’s political actions, he appeals also to his compatriots’ national sentiments. By the fact that the relationship of the Hungarian rulers with the Slavic ethnicity and its language is positive, he indirectly encourages them to cultivate their mother tongue. He gives the conversation also distinctive religious characteristics, he points out the connection between the earthly and the eternal life, since it is only immortality that gives purpose to the ruler’s earthly journey.